2022
DOI: 10.1101/2022.12.28.22283999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Same-day testing with initiation of antiretroviral therapy or tuberculosis treatment versus standard care for persons presenting with tuberculosis symptoms at HIV diagnosis: A randomized unblinded trial

Abstract: Background: Same-day HIV testing and antiretroviral therapy (ART) initiation is being widely implemented. However, the optimal timing of ART among patients with tuberculosis (TB) symptoms is unknown. We hypothesized that same-day treatment would be superior to standard care in this population. Methods and Findings: We conducted an open-label randomized trial among adults with TB symptoms at initial HIV diagnosis at GHESKIO in Haiti. Participants were randomized in a 1:1 ratio to same-day treatment (same-day TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…SaDAPT is a pragmatic randomized non-inferiority trial conducted in Malawi and Lesotho that compares the effectiveness and safety of SDI of ART ("ART first") to ART initiation only after results of TB investigations are available ("TB results first") in PWH with presumptive TB. A previous trial assessing the effectiveness of SDI in presumptive TB has provided same-day NAAT results as part of the trial procedures and then started ART only in participants found to be TB negative (42). However, this turnaround time for NAAT is not feasible in many settings.…”
Section: Discussionmentioning
confidence: 99%
“…SaDAPT is a pragmatic randomized non-inferiority trial conducted in Malawi and Lesotho that compares the effectiveness and safety of SDI of ART ("ART first") to ART initiation only after results of TB investigations are available ("TB results first") in PWH with presumptive TB. A previous trial assessing the effectiveness of SDI in presumptive TB has provided same-day NAAT results as part of the trial procedures and then started ART only in participants found to be TB negative (42). However, this turnaround time for NAAT is not feasible in many settings.…”
Section: Discussionmentioning
confidence: 99%
“…We included all participants enrolled in the original trial in this secondary analysis. 12 Patients were eligible for inclusion in the trial if they had documented HIV-1 infection, were ≥18 years of age, ART-naïve, and reported cough, fever, and/or night sweats of any duration, and/or weight loss. Exclusion criteria included tuberculosis treatment in the past year, lack of preparedness on an ART readiness questionnaire, pregnancy or breastfeeding, active drug or alcohol use, a mental condition that would interfere with completing study requirements, plans to transfer during the study period, symptoms consistent with WHO stage 4 neurologic disease, or WHO "danger signs" of temperature >39 degrees Celsius, pulse >120 beats/minute, respiratory rate >30 breaths/minute, or inability to walk unaided.…”
Section: Study Populationmentioning
confidence: 99%
“…Study procedures have been reported in detail elsewhere. 12 For the purposes of this analysis, we included baseline demographic, clinical and laboratory data, as well as outcome data 48 weeks after enrollment, all of which were extracted from the GHESKIO electronic health record. Baselines variables included in this analysis were: age, sex, income less than $1 USD per day (self-report), educational attainment, marital status, body mass index (BMI), CD4 cell count, tuberculosis diagnosis (microbiologically or clinically diagnosed), and study arm (same-day or standard).…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations